REGISTER ANALYSIS IN ACTION FIGURE TRADING FORUM ON KASKUS - WARDHANA, RAMADHITA ADHITYA (Jurnal Ilmiah Mahasiswa FIB, 2013)
The internet eases social interaction. Besides, it becomes a medium to build community and people use social network to create certain groups. But still, they use language to deal with it. In communication purpose, people intentionally use a specific language variety namely register in their own community. The register can make people who do not belong to the member misinterpret the meaning because they do not know about the three kinds of variation which construct the context of register itself; they are field, mode and tenor.This study uses Halliday’s theory to analyze the register which is used by action figure trading member on Kaskus. There are two research problems in this research: (1) what are the registers used by the members of action figure trading forum on Kaskus tenor applied in statements or conversation made by the members of action figure trading forum on Kaskus?Keywords: register, action figure trading forum, Kaskus. This study uses qualitative approach to make it clear and systematic to analyze. As the data, the writer uses action figure trading terms from Kaskus as keywords to find the register applications in action figure trading forum on Kaskus research design to identify specified characteristics of the materials.The finding shows 14 registers found. The language variety belongs to register because it is only used and can only be understood by the members. The register consists of 10 terms which similar with ordinary words form and the rest 4 terms are not familiarly used in common language. The register only has particular meaning. The terms use is determined by the context which influences the activities because the situational factors like field, mode and tenor are the main factors to determine the purpose in using register. The register helps the members to simplify the language, to recognize the member and to decrease certain probability of deceit. Then the members always use informal talk and they always intend to build a seller-customer and a customer-customer relationship.As a conclusion, the writer realizes that register variables consist of field,mode and tenor are not the only device to analyze the register phenomenon.Moreover, he focuses this research only on the vocabulary meaning. Therefore, he suggests the next researcher to use another way to analyze a register phenomenon and conduct a research in a different social network in many different points of view.